Іншомовні запозичення в українській термінології - Коновалова, Олександра; Комова, Марія (Видавництво Львівської політехніки, 2016)
Ukrainian terminology was formed mainly on national lexical basis. However, it is constantly replenished by direct and indirect lexical borrowing from genetically related and unrelated languages, what was led by ekonomical, political and cultural communications carriers. Penetration of foreign components in terminology system was caused by the fact that national generally employed can not represent all the achievements of human experience in the knowledge of the world. Economic and spiritual development of society lead to the appearance of many different words by their origins for marking new notions.
Keywords: social communications; document; іншомовні запозичення terms forming; werb-forming model